2021
DOI: 10.1099/ijsem.0.005140
|View full text |Cite
|
Sign up to set email alerts
|

Gracilibacillus suaedae sp. nov., an indole acetic acid-producing endophyte isolated from a root of Suaeda salsa

Abstract: A Gram-stain-positive, facultatively anaerobic, spore-forming, motile with unipolar biflagella, rod-shaped, indole acetic acid-producing bacterium, named LD4P30T, was isolated from a root of Suaeda salsa collected in Inner Mongolia, northern China. Strain LD4P30T grew at pH 6.0–11.0 (optimum, pH 7.0), 10–40 °C (35 °C) and in the presence of 1–15% (w/v) NaCl (5%). The strain was positive for oxidase and negative for catalase. The major cellular fatty acids of strain LD4P30T were iso-C15:0, C15:1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…This genus was isolated from high-salt environments such as salt fields and fermented food [ 43 , 44 ]. Huang et al [ 45 ] found that several strains of Gracilibacillus produce indole acetic acid, a product of the gut microbiota in uremic patients. Previous studies revealed indole acetic acid-induced cardiac injury in patients with end-stage renal disease, including cardiac hypertrophy and diastolic dysfunction [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This genus was isolated from high-salt environments such as salt fields and fermented food [ 43 , 44 ]. Huang et al [ 45 ] found that several strains of Gracilibacillus produce indole acetic acid, a product of the gut microbiota in uremic patients. Previous studies revealed indole acetic acid-induced cardiac injury in patients with end-stage renal disease, including cardiac hypertrophy and diastolic dysfunction [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, all the strains have been generally studied for tolerance to salt and reported to be halotolerant to moderately halophilic in nature. Even species isolated from ecological niches such as fermented fish, kimchi, seeds, roots and fermentation liquor have been found to tolerate up to 22 % (w/v) NaCl and exhibit optimum growth with 1-10 % NaCl [13][14][15][16][17]. Following tolerance to salinity, DNA G+C content at a range of 35.0-43.0 %, the presence of menaquinone-7 (MK-7) as the major respiratory quinone, meso-diaminopimelic acid (meso-DAP) as the cell-wall diamino acid, diphosphatidylglycerol and phosphatidylglycerol as the major polar lipids and iso-C 15 : 0 , anteiso-C 15 : 0 and anteiso-C 17 : 0 as major fatty acids help in the assignment of species to the genus Gracilibacillus [1,6,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Even species isolated from ecological niches such as fermented fish, kimchi, seeds, roots and fermentation liquor have been found to tolerate up to 22 % (w/v) NaCl and exhibit optimum growth with 1-10 % NaCl [13][14][15][16][17]. Following tolerance to salinity, DNA G+C content at a range of 35.0-43.0 %, the presence of menaquinone-7 (MK-7) as the major respiratory quinone, meso-diaminopimelic acid (meso-DAP) as the cell-wall diamino acid, diphosphatidylglycerol and phosphatidylglycerol as the major polar lipids and iso-C 15 : 0 , anteiso-C 15 : 0 and anteiso-C 17 : 0 as major fatty acids help in the assignment of species to the genus Gracilibacillus [1,6,[15][16][17]. Saline environments have been consistently recorded in scientific literature as an excellent source of microorganisms that have huge biotechnological potential in the areas of agriculture, industry, bio-medicine, bioremediation and biofuels [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…During an ongoing research project on the isolation and characterization of beneficial bacteria from halophytes [7,[11][12][13][14], an ACC deaminase-producing bacterium, designated M5D2P5 T which was isolated from a root of Kalidium cuspidatum, had low 16S rRNA gene similarities with all the current type strains. The characterization of this strain using a polyphasic taxonomy approach is described in this paper.…”
Section: Introductionmentioning
confidence: 99%